2016
DOI: 10.1038/nchembio.2202
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of nonribosomal peptide macrocyclization in fungi

Abstract: Nonribosomal peptide synthetases (NRPSs) in fungi biosynthesize important pharmaceutical compounds, including penicillin, cyclosporine and echinocandin. To understand the fungal strategy of forging the macrocyclic peptide linkage, we determined the crystal structures of the terminal condensation like (CT) domain and the holo T-CT complex of Penicillium aethiopicum TqaA. The first structural depiction of the terminal module in fungal NRPS provides a molecular blueprint for generating novel macrocyclic peptide n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 31 publications
4
83
0
3
Order By: Relevance
“…Many examples of assembly line ACPs docking with cognate enzymes are known, even though all are from NRPS modules. Representative interactions between ACPs and embedded assembly line enzymes have been observed for the C domain (donor site: PDB 5EJD, acceptor site: PDB 4ZXH), the A domain (PDBs 4DG9), the epimerization (E) domain (PDB 5ISX), and the thioesterase (TE) domain (PDB 3TEJ). Representative interactions between an ACP and a non‐embedded P450 monooxygenase have also been observed (PDB 4PXH).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many examples of assembly line ACPs docking with cognate enzymes are known, even though all are from NRPS modules. Representative interactions between ACPs and embedded assembly line enzymes have been observed for the C domain (donor site: PDB 5EJD, acceptor site: PDB 4ZXH), the A domain (PDBs 4DG9), the epimerization (E) domain (PDB 5ISX), and the thioesterase (TE) domain (PDB 3TEJ). Representative interactions between an ACP and a non‐embedded P450 monooxygenase have also been observed (PDB 4PXH).…”
Section: Resultsmentioning
confidence: 99%
“…assembly line ACPs was investigated.Many examples of assembly line ACPs docking with cognate enzymes are known, even though all are from NRPS modules. Representative interactions between ACPs and embedded assembly line enzymes have been observed for the C domain (donor site: PDB 5EJD,27 acceptor site: PDB 4ZXH28 ), the A domain (PDBs 4DG929 ), the epimerization (E) domain (PDB 5ISX30 ), and the thioesterase (TE)FIG URE 3 Cladograms of KSs Upstream and Downstream of ACPs Support the Updated Module Boundaries. A, The lack of clustering for KSs upstream of ACPs that clade together, with the anticipated exception of KSs from the first module of bimodules, indicates ACPs do not usually evolutionarily co-migrate with the KS upstream of them.…”
mentioning
confidence: 97%
“…Instead, the free TE gene may fulfill an editing function during metabolite biosynthesis (22). We found that the terminal C domain of SimA could be grouped together with those C T domains being functionally verified to catalyze the cyclization of macrocycles, e.g., the C T domain of the NRPS TqaA from Penicillium aethiopicum (21, 23). It is suggested therefore that the terminal C domain of SimA might contribute to the release and cyclization of CSNs.…”
Section: Discussionmentioning
confidence: 99%
“…Additional C domains were also retrieved from the nonribosomal peptide synthetase (NRPS) DtxS1 for destruxin biosynthesis in Metarhizium spp. (27), and the beauvericin nonribosomal cyclodepsipeptide synthetase (BEAS) for the production of beauvericin in B. bassiana (29) as well as the cyclization C T domains of Penicillium aethiopicum TqaA (21, 23) and Emericella rugula EcdA (41). The A- or C-domain sequences were aligned with the program Clustal X (ver.…”
Section: Methodsmentioning
confidence: 99%
“…Recent structures have been obtained with pantetheine chains bound to the acceptor site. 56, 58 While no structures exist of a condensation domain bound to a donor PCP, structures of TqaA, the homologous terminal cyclization domain of fungal NRPSs, 62 and an epimerization domain of the gramicidin synthetase GrsA 57 provide models for the binding of the PCP to the condensation domain donor site.…”
Section: The Biochemistry and Structural Biology Of The Nonribosommentioning
confidence: 99%